Poly(p-xylene disulfide) and poly(p-xylene tetrasulfide): synthesis, cure and investigation of mechanical and thermophysical properties. Issue 1 (17th September 2020) - Sheydaei, Milad; Edraki, Milad; Alinia-Ahandani, Ebrahim; Rufchahi, Enayat Ollah Moradi; Ghiasvandnia, Pegah
Abstract: In this work, two polysulfide polymers were synthesized using aromatic organic monomer (α, α′-dichloro- p -xylene) and sodium disulfide (Na2 S2 ) and sodium tetrasulfide (Na2 S4 ) aqueous monomers. Then, the curing process of the polymers was carried out at 170° C using a rheometer. The structural characteristics of synthesized and cured samples were identified by Raman and Fourier transform infrared (FT-IR) spectroscopies. Also, morphological and thermophysical properties of samples were studied by using the X-ray diffraction (XRD) and differential scanning calorimetry (DSC), respectively. Moreover, the molecular weight of the synthesized samples was determined by proton nuclear magnetic resonance ( 1 H NMR). Furthermore, the mechanical properties and hardness of the samples were investigated by tensile test and Shore A. The results showed that in the noncured samples during the increase of sulfur in the polymer structure, solubility was increased whereas it decreased the hardness, melting point ( Tm ) and glass transition temperature ( Tg ) of polymers. But in cured samples, hardness and Tg increase by increasing sulfur and the mechanical properties also improved. This is due to the increase in crosslinks. Also, Tm and solubility are not observed due to the formation of crosslinks. Graphical Abstract: